홍삼산성다당체 (RGAP)와 항암제의 병용투여에 의한 항암시너지 효과 - 곽이성(Yi-Seong Kwak); 김영숙(Young-Sook Kim); 신한재(Han-Jae Shin); 송용범(Yong-Bum Song); 박종대(Jong-Dae Park) (Journal of ginseng research, 2003)
Synergistic anticancer activities of red ginseng acidic polysaccharide (RGAS) showing immunomodulatory activity were evaluated by combined treatment with anticancer agents such as Cyclophosphamide (CY) or 5-Fluorouracil (5-FU) in experimental tumor models. The combined treatment of RGAP (100 mg/kg) and CY (3 mg/kg) exhibited 71% of survival rate in lift span of sarcoma 180-bearing mice, while single treatment of RGAP (100 mg/kg) and CY (3 or 10 mg/kg) exhibited 43, 14 and 43% of survival rates, respectively. In addition, when RGAP (100 mg/kg) was administered in combination with 5-FU (2.5 mg/kg) to sarcoma 180 tumor-bearing mice, higher survival rate was found when compared with RGAP or 5-FU treatment alone. Moreover, tumor weights in LL/2 lung carcinoma-bearing mice treated combined with RGAP (100 mg/kg) and 5-FU (5 or 10 mg/kg) was obviously decreased when compared with 5-FU alone. These results suggest that clinical trials of RGAP as an adjuvant in cancer chemotheraphy can be higly feasible. Sarcoma 180 암세포를 이식한 마우스에서 면역조절 작용을 갖는 홍삼산성다당체 (RGAP)를 항암제 cyclophosphamide (CY)와 병용투여한 결과, RGAP (100 mg/kg)와 CY (3 mg/kg)의 병용투여는 고용량의 CY (10 mg/kg) 단독투여보다 강한 항암작용을 나타내었다. 또한 RGAP (100 mg/kg)과 CY (10 또는 20 mg/kg)과의 병용투여는 CY의 단독투여보다 LL/2 폐종양을 보다 강하게 억제하였다. RGAP (100 mg/kg) 와 5-fluorouracil (5-FU) (2.5 mg/kg)을 병용투여하였을 때도 sarcoma 180 암세포를 이식한 마우스에서 5-FU 단독투여군에 비해 현저한 항암시너지 효과를 나타내었다. LL2 폐 종양에 미치는 결과에서도 RGAP (100 mg/kg)와 5-FU (5 또는 10 mg/kg) 병용투여군은 항암제 단독투여군보다 강한 항종양 효과를 나타내었다. 이상의 결과로부터 RGAP는 항암제 CY 또는 5-FU와 병용투여시 sarcoma 180 및 LL/2 폐종양에 대해서 저용량 항암제의 사용으로 고용량의 항암제 사용에서와 유사한 항암효과를 나타낼 수 있어서 항암효과를 극대화 시킬뿐만아니라 항암제 사용에 의한 면역독성과 같은 부작용을 경감시킬 수 있는 항암치료 보조제로서의 사용가능성을 제시하였다.